Retail blues in black and white: an emerging market context. Issue 11 (10th December 2018) - Pandey, Pallavi; Singh, Saumya; Pathak, Pramod
Abstract : Purpose: Research investigating turnover intention among frontline employees in the Indian retail industry is scarce. The purpose of this paper is to explore factors affecting withdrawal cognitions among front-end retail employees in India. Design/methodology/approach: Semi-structured interviews were conducted to explore the factors responsible for developing turnover intentions among the front-end employees. Data were analyzed using the ground theory approach. Findings: Qualitative investigation revealed nine factors (abusive supervision, favoritism, perceived job image, insufficient pay, work exhaustion, perceived unethical climate, organization culture shock, staff shortage and job dissatisfaction) are responsible for developing turnover intention among front-end employees in the Indian retail industry. Originality/value: The study uncovers antecedents of turnover intention among front-end employees in the relatively neglected Indian retail sector through a qualitative technique. Theoretical contributions, managerial implications, limitations and direction for future research are discussed.